2018
DOI: 10.2134/jeq2018.01.0054
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Persulfate and Potassium Permanganate Inhibit Methanogens and Methanogenesis in Stored Liquid Dairy Manure

Abstract: Stored liquid dairy manure is a hotspot for methane (CH) emission, thus effective mitigation strategies are required. We assessed sodium persulfate (NaSO), potassium permanganate (KMnO), and sodium hypochlorite (NaOCl) for impacts on the abundance of microbial communities and CH production in liquid dairy manure. Liquid dairy manure treated with different rates (1, 3, 6, and 9 g or mL L slurry) of these chemicals or their combinations were incubated under anoxic conditions at 22.5 ± 1.3°C for 120 d. Untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…As a strong oxidizing agent, KMnO 4 is capable of inactivating methanogens by oxidizing the key metabolic coenzyme F 420 . Xu et al found that the chemical oxygen demand (COD) content used for CH 4 production decreased from 4.77% ± 0.05% to 0.02% ± 0.01% and the specific activity of methanogens declined by 73.3% when the KMnO 4 dosage increased from 0 to 0.2 g/g total suspended solids (TSS). Furthermore, KMnO 4 can also combine with other agents to change the methanogenic community, exerting a more significant effect than a single-KMnO 4 pretreatment.…”
Section: Approaches To Suppress Methane Production In Mecsmentioning
confidence: 99%
“…As a strong oxidizing agent, KMnO 4 is capable of inactivating methanogens by oxidizing the key metabolic coenzyme F 420 . Xu et al found that the chemical oxygen demand (COD) content used for CH 4 production decreased from 4.77% ± 0.05% to 0.02% ± 0.01% and the specific activity of methanogens declined by 73.3% when the KMnO 4 dosage increased from 0 to 0.2 g/g total suspended solids (TSS). Furthermore, KMnO 4 can also combine with other agents to change the methanogenic community, exerting a more significant effect than a single-KMnO 4 pretreatment.…”
Section: Approaches To Suppress Methane Production In Mecsmentioning
confidence: 99%
“…Decreasing the concentration of greenhouse gases in the atmosphere and regulating their emissions, as well as reducing fire-hazardous situations in landfills where methane is released, is considered today as an important environmental task [78]. In the course of developing strategies to reduce most methane emissions, various chemical or biochemical agents that affect or alter the metabolic activity of cells that are part of methanogenic compounds, are used [61,79,80].…”
Section: The Use Of Bioluminescent Atp-assay In the Development Of St...mentioning
confidence: 99%